The navigator's paradox: how digital game addiction transforms spatial orientation through serial mediation by sense of direction and spatial anxiety - Akin, Ayca; Alkan, Selcuk; Sezgin, Hayriye Seda; Guzeller, Cem Oktay (TAYLOR & FRANCIS LTD, 2026)
Digital games are part and parcel of modern life, where millions of people from all walks of life engage in one kind of gaming or another every day. This phenomenon has led to research examining the cognitive/psychological effects of digital game addiction, particularly concerning spatial skills. This study investigated whether digital game addiction is related to spatial orientation skills via the mediating roles of sense of direction and spatial anxiety. The data were collected from a sample of 1,030 undergraduate students through a mixed-methods approach and showed that higher addiction risk related to improved spatial orientation skills was partially mediated by a stronger sense of direction and reduced spatial anxiety. The qualitative analysis revealed diverging patterns: the participants who were at a moderate to high risk of addiction boasted their spatial orientation skills and reported a higher sense of direction, and lesser spatial anxiety, favouring cognitively challenging games such as action and adventure. Conversely, low-risk participants reported lesser spatial orientation skills, a lower sense of direction, and higher spatial anxiety, favouring social-casual games with less cognitively demanding. This research contributes to the understanding of the cognitive impact of digital gaming by providing insights into how gaming habits affect spatial skills.
Keywords: Digital game addiction; sense of direction; spatial anxiety; spatial orientation skills; undergraduate students; VIDEO GAMES; GENDER-DIFFERENCES; MENTAL-ROTATION; WORKING-MEMORY; INDIVIDUAL-DIFFERENCES; ATTENTIONAL CONTROL; SELF-DETERMINATION; BRAIN PLASTICITY; COGNITIVE MAPS; ABILITY; Computer Science; Engineering